La grammatica araba: scienza sacra e chiave per l’esegesi coranica (Doctor Virtualis, 2022)
In this article I reflect on the emergence of Arabic grammar and its development as a source for Qur’ān exegesis from VIII to XIV century. The connection between exegesis and grammar has been the subject of several studies examining the origin of grammatical categories. Although there is no evidence of a clear interest for grammar by Qur’ān exegetes, they necessarily used it to explain the meanings of the sacred text. In particular, in the classical commentaries there is a particular attention to lexicography and less to the grammatical structure. However, in some passages, even if sporadic, the grammatical categories themselves perform an explanatory function, being bearers of meanings. This is manifest in Sufi literature where Arabic grammar terminologies are symbols of the stations of souls in the spiritual path, like in the Grammar of the heart by al-Qushayrī. In this article, I analyse the status of grammar in Quranic Sciences according to the theologian al-Ghazālī and after an overview on the history of the discipline in the classical period of Islamic History, and I highlight the way grammar terminologies serve as a key to understand profound meaning in sura al-Fātiha in Ibn Kathīr’s sunni commentary.
Keywords: Qur’ān Exegesis; Grammar; al-Ghazālī; Ibn Kathīr